Risk of cardiac manifestations in adult mitochondrial disease caused by nuclear genetic defects. Issue 1 (1st April 2021) - Lim, Albert Zishen; Jones, Daniel M; Bates, Matthew G D; Schaefer, Andrew M; O'Sullivan, John; Feeney, Catherine; Farrugia, Maria E; Bourke, John P; Turnbull, Doug M; Gorman, Gráinne S; McFarland, Robert; Ng, Yi Shiau
Abstract : Objective: Regular cardiac surveillance is advocated for patients with primary mitochondrial DNA disease. However, there is limited information to guide clinical practice in mitochondrial conditions caused by nuclear DNA defects. We sought to determine the frequency and spectrum of cardiac abnormalities identified in adult mitochondrial disease originated from the nuclear genome. Methods: Adult patients with a genetically confirmed mitochondrial disease were identified and followed up at the national clinical service for mitochondrial disease in Newcastle upon Tyne, UK (January 2009 to December 2018). Case notes, molecular genetics reports, laboratory data and cardiac investigations, including serial electrocardiograms and echocardiograms, were reviewed. Results: In this cohort-based observational study, we included 146 adult patients (92 women) (mean age 53.6±18.7 years, 95% CI 50.6 to 56.7) with a mean follow-up duration of 7.9±5.1 years (95% CI 7.0 to 8.8). Eleven different nuclear genotypes were identified: TWNK, POLG, RRM2B, OPA1, GFER, YARS2, TYMP, ETFDH, SDHA, TRIT1 and AGK . Cardiac abnormalities were detected in 14 patients (9.6%). Seven of these patients (4.8%) had early-onset cardiac manifestations: hypertrophic cardiomyopathy required cardiac transplantation ( AGK; n=2/2), left ventricular (LV) hypertrophy and bifascicular heart block ( GFER; n=2/3) and mild LV dysfunction ( GFER; n=1/3, YARS2; n=1/2, TWNK; n=1/41). The remaining seven patients had acquired heart disease most likely related to conventional cardiovascular risk factors and presented later in life (14.6±12.8 vs 55.1±8.9 years, p<0.0001). Conclusions: Our findings demonstrate that the risk of cardiac involvement is genotype specific, suggesting that routine cardiac screening is not indicated for most adult patients with nuclear gene-related mitochondrial disease.